IDENTIFICATION OF ENVIRONMENTALLY FISHING GEARS IN CAROCOK TARUSAN COASTAL FISHING PORT WEST SUMATERA PROVINCE (CASE STUDY OF FISHING GEAR BOAT LIFT NET AND PALAGIC DANISH SEINE) - Intan Wardika Putri; Arthur Brown; Isnaniah Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract This study was conducted on 9-17 june 2018, is located in Carocok Tarusan coastal fishing port west, Sumatera Barat. The purpose of this study was to determine the level of environmental friendliness of fishing gear operating in the Carocok Tarusan coastal fishing port, whether it is in accordance with FAO rules or guided by 9 CCRF criteria (1995). The method used in this study is the survey method, by making direct observations and filling out questioneres by the panelists. The object under study is a boat lift net and palagic danish seine fishing gear.as well as deep interview and questioneresand analyzed using descriptive analysis of the results of the research described in graphic form, and tables. The results showed that the boat lift net and palagic danish seine fishing gear used by fishermen in the Carocok Tarusan coastal fishing port was an ecofriendly boat lift net fishing gear with a score of 27,78 and palagic danish seine fishing gear which was also classified as an ecofriendly fishing gear with a total score of 26,27.Keywords : Carocok Tarusan Coastal Fishing Port, CCRF, Fishing gears